Existence of Microplastics in Indonesia's Surface Water: A Review - Ali, Firdaus; Azmi, Khalidah Nurul; Firdaus, Madina Rain (International Journal of Integrated Engineering, 2021)
Plastic waste is often being an issue that needs to be overcome since mostly plastic waste ends up in the environment. Some studies stated that plastic waste found in the marine environment are mostly sourced from the land which transported along the river systems. It is nearly impossible for nature to completely breakdown plastic waste, regarding its durability and resistance to degradation. Small fragment resulted from the slowly breakdown of plastic waste is an emerging contaminant in water environment called as microplastic. This study is conducted as a short review of microplastics existence on the surface water in Indonesia, particularly on the Citarum River as the most polluted river in the world. Besides, only few papers regarding microplastic occurrence on the surface water in Indonesia that have been published, which mostly focuses on Citarum River. It is known that microplastic tend to persist in water and has possible risks to the living organisms. Hence, managing microplastic pollution is needed which can be in the form of management strategy and treatment technologies used to remove microplastics from water.